MEDICAL AND SOCIOLOGICAL RESEARCH ON PUBLIC SATISFACTION WITH THE SERVICES PROVIDED BY THE CONSULTATIVE AND DIAGNOSTIC CENTER - Кулешов, Владимир (SWorldJournal, 2021)
Patient satisfaction with the quality of health care services tends to be the top-priority issue for health care facilities. The survey using questionnaires, making for the study of patient opinions and finding out patient satisfaction with online medical